Lipoblastoma of the abdominal wall - Filipa Jalles; Patrícia Lipari Pinto; Ana Paula Martins; Miroslava Gonçalves (Elsevier, 2019)
Lipoblastoma/Lipoblastomatosis is a rare benign neoplasm that derives from embryonic adipose tissue, most often encountered as a rapidly growing painless mass in infants and children. The treatment of choice includes a complete, but conservative excision and surveillance of recurrence. Long-term follow-up is required since this tumor locally recurs in up to 25% of the cases. The authors describe a 13-year-old female who underwent tumor resection of a mass localized in the abdominal wall. A complete resection was undertaken, with histopathology report confirming the diagnosis of lipoblastoma. She maintains free of disease with a follow-up of 8 months. A relevant literature review was done. The authors want to make aware of and remind this rare entity when diagnosing children with rapid-growing mass and also describe current management paradigms for this uncommon tumor. Keywords: Lipoblastoma, Pediatric, Benign tumor